2022
DOI: 10.1002/sys.21641
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative validation of complex systems integration principles

Abstract: The integration of complex systems is an important aspect of systems engineering.Previous research derived six integration principles and qualitatively validated four of them using a data set of 14 systems. Of the two non-validated principles, one was determined to be confounded with two of the four validated principles and is hence not considered in this research. This paper describes the quantitative validation of the resulting five integration principles based on an expanded data set of 52 systems. This exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Grumbach and Thomas defined the Principle of Reuse and Evolvability that allowed for existing components to adapt to new applications with a small increase in system complexity and a large decrease in uncertainty 17 . Grumbach and Thomas further validated their results and found that success in component reuse is affected by adherence to hierarchic verification approaches and treating subsystem integration as part of full system integration 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grumbach and Thomas defined the Principle of Reuse and Evolvability that allowed for existing components to adapt to new applications with a small increase in system complexity and a large decrease in uncertainty 17 . Grumbach and Thomas further validated their results and found that success in component reuse is affected by adherence to hierarchic verification approaches and treating subsystem integration as part of full system integration 18 …”
Section: Introductionmentioning
confidence: 99%
“…17 Grumbach and Thomas further validated their results and found that success in component reuse is affected by adherence to hierarchic verification approaches and treating subsystem integration as part of full system integration. 18 Other researchers have explored reinforcement learning algorithms more generally to improve their performance against complex problem sets. Gupta, Roy, and Dutt compared Instance-Based Learning (IBL) and Q-Learning algorithms in a dynamic test environment and found that IBL is more effective for dynamic environments.…”
Section: Introductionmentioning
confidence: 99%